Predicting coronal mass ejections transit times to Earth with neural network - Sudar, D.; Vršnak, B.; Dumbović, M. (Monthly notices of the Royal Astronomical Society, 2016)
Predicting transit times (TT) of coronal mass ejections (CMEs) from their initial parameters is a very important subject, not only from the scientific perspective, but also because CMEs represent a hazard for human technology. We used a neural network (NN) to analyse TT for 153 events with only two input parameters: initial velocity of the CME, v, and central meridian distance, CMD, of its associated flare. We found that transit time dependence on v is showing a typical drag-like pattern in the solar wind. The results show that the speed at which acceleration by drag changes to deceleration is v ≈ 500 km s−1. TT are also found to be shorter for CMEs associated with flares on the western hemisphere than those originating on the eastern side of the Sun. We attribute this difference to the eastward deflection of CMEs on their path to 1 au. The average error of the NN prediction in comparison to observations is ≈12 h which is comparable to other studies on the same subject.